Laboratory Evaluation and Design of Construction and Demolition Wastes for Granular Base - Jin Yi; Chenghao Liang; Junfeng Qian; Jue Li; Yongsheng Yao (Advances in Civil Engineering)
Using recycled aggregate from construction and demolition (C&D) wastes as a construction material is a potential method for solving the disposal of C&D wastes, which can reduce the exploitation of natural aggregate. In this study, extensive laboratory tests were carried out to investigate the reliability of the C&D wastes used as road base material. Meanwhile, the gradation design and the dominant aggregate size range were considered, and a physical disposal method was proposed to enhance the structural performance of the recycled material by replacing the skeleton of the recycled aggregate (RA) with high-quality limestone. The test results showed that (1) given the high absorbency and fragility of C&D wastes, its RA was not enough to provide the strength and stability required by the base; (2) the compaction characteristics of the RA are quite different from that of the limestone aggregate, but the final compaction effect is basically the same; (3) the replacement treatment proposed in this study is an effective approach to improve the performance of the recycled granular base because the breakage rate decreased by at least 28.2% and the mechanical properties increased by approximately 50% compared with that of the untreated specimen; and (4) when the limestone content reached 75%, the California bearing ratio and the resilient modulus of the graded B specimen exceeded 120% and 200 MPa, respectively, satisfying the pavement requirement in medium traffic.